The decline of the indigenous languages of Equatorial Guinea: a manifestation of the loss of cultural identity - Bituga-Nchama, Pedro (2021)
This study focuses on the analysis of the sociolinguistic situation in Equatorial Guinea. In this sense, it starts from the fact that the lack of learning of the country's native languages has led to a loss of cultural identity, which has been aggravated by other factors such as globalization. The little importance given to indigenous languages means that all of them are undergoing changes that would cause their decline and subsequent disappearance. Invest should be made in language policies that can counteract this effect because when a language disappears, so does a part of the same culture. It is important to note that this research is not anchored in linguistic relativism because it recognizes that promoting indigenous languages is not a way to veto the official languages of the country.At present there is a loss of cultural identity motivated by the fact that children are not taught indigenous languages, they pretend that they are polyglot or bilingual without their own linguistic base: we refer to their indigenous languages that identify them as part of a group or community. Throughout this work, it becomes clear that there cannot be cultural policies without language policies, because people should know the indigenous languages of their culture. In fact, the main results of this research show the need to protect autochthonous languages, it is incoherent to promote Spanish to the detriment of autochthonous languages that represent the identity of each ethnic group.